Studies on seed development, quality and physiological maturity in marigold (Tagetes spp.) - V.S. MOR; D.P. DESWAL; B.S. BENIWAL; B.S. DAHIYA (Seed Research, 2026)
Marigold (Tagetes spp.) is an important commercial ornamental flower crop of India. To investigate the seed development and seed quality as well as physiological maturity, nine genotypes consists of Tagetes erecta L. and Tagetes patula L. were planted following standard agronomical practices. The flower buds of all nine genotypes were tagged from the initiation of anthesis. The flowers from both species were harvested at the seven different developmental stages i.e. 0th, 7th, 14th, 21th, 28th, 35th and 42nd days from anthesis (DFA). The investigations indicated that the attainment of physiological maturity occurred 35th DFA in T. erecta and 28th DFA in T. patula which was associated with dark black seed colour, withering of petals, yellowing of capitulum and peduncle as morphological indices of seed maturity.